2005
DOI: 10.1007/s10546-005-0905-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multi-Layer Urban Canopy Model for the Analysis of Energy Consumption in a Big City: Structure of the Urban Canopy Model and its Basic Performance

Abstract: A multilayer one-dimensional canopy model was developed to analyze the relationship between urban warming and the increase in energy consumption in a big city. The canopy model, which consists of one-dimensional diffusion equations with a drag force, has three major parameters: building width, distance between buildings, and vertical floor density distribution, which is the distribution of a ratio of the number of the buildings that are taller than some level to all the buildings in the area under consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(113 citation statements)
references
References 26 publications
(28 reference statements)
4
105
0
4
Order By: Relevance
“…There have been studies that have used modeling frameworks other than WRF (e.g. Loridan et al, 2013;Bohnenstengel et al, 2011;Kondo et al, 2005;Masson et al, 2000) that aimed to more accurately represent the complex processes that occur in these environments. The inaccuracies have been well documented (Best and Grimmond, 2015) and there have been studies done that have utilized parameterization techniques and different model schemes to try and get better agreement between the model and the observations (e.g.…”
Section: Pbl and Lsm Scheme Sensitivity And Improving Simulations Ovementioning
confidence: 99%
“…There have been studies that have used modeling frameworks other than WRF (e.g. Loridan et al, 2013;Bohnenstengel et al, 2011;Kondo et al, 2005;Masson et al, 2000) that aimed to more accurately represent the complex processes that occur in these environments. The inaccuracies have been well documented (Best and Grimmond, 2015) and there have been studies done that have utilized parameterization techniques and different model schemes to try and get better agreement between the model and the observations (e.g.…”
Section: Pbl and Lsm Scheme Sensitivity And Improving Simulations Ovementioning
confidence: 99%
“…Masson, 2000;Kusaka et al, 2001;Lee and Park, 2008;Oleson et al, 2008) and the multilayer schemes (e.g. Martilli et al, 2002;Dupont et al, 2004;Kondo et al, 2005). The former group of UCM usually focuses on parametrization of surface energy budgets and has been adopted in the Weather Research and Forecasting (WRF) model (Chen et al, 2011), whereas the latter group attempts to also better represent the flow dynamics induced in urban canopies, although the flow is still parametrized rather than resolved as for example in direct (Coceal et al, 2006) or large-eddy (Bou-Zeid et al, 2009) turbulence simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In [2,[3][4][5][6][7][8][9][10][11][12][13][14][15][16] it is shown that the average CHTC on the windward façade is not very sensitive to wind direction so that a wind direction of 45° from the normal can represent a wide range of wind directions between 0° and 60°.…”
Section: Cfd Numerical Modelmentioning
confidence: 99%